The harms of work : an ultra-realist account of the service economy / Anthony Lloyd. - Lloyd, Anthony (Studies in social harm., 2018)
This book discusses workplace harm through an ultra-realist lens and examines the connection between individuals, their working conditions and management culture. It investigates the reorganisation of labour markets and the shift to flexibility, and highlights working conditions and organisational practices within which multiple harms occur.